2018
DOI: 10.1080/02713683.2018.1490435
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Slit Lamp Anterior Segment Photography versus Digital Compact Camera Mounted on a Standard Slit Lamp with an Adapter

Abstract: DCC on slit lamp with an adaptor is comparable to a SLC. There is an initial learning curve, which is similar for both for an inexperienced person. This opens up the possibility for low cost anterior segment imaging in the clinical, research, and teaching settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…By shining a thin sheet of light into the eye, an in vivo stereoscopic evaluation of the pathological changes of the cornea, conjunctiva and other anterior segment tissues can be performed by SLB [9]. However, the limited magnification and poor spatial resolution of traditional SLB make it difficult to visualize more detailed pathological structures and perform accurate biometric measurements [10][11][12]. Fluorescein stain could stain stroma while leaving the intact epithelium with a specific fluorescein dye, thereby demarcating the location and area of the epithelial loss in ocular surface diseases, on a relative macro scale as well [13].…”
mentioning
confidence: 99%
“…By shining a thin sheet of light into the eye, an in vivo stereoscopic evaluation of the pathological changes of the cornea, conjunctiva and other anterior segment tissues can be performed by SLB [9]. However, the limited magnification and poor spatial resolution of traditional SLB make it difficult to visualize more detailed pathological structures and perform accurate biometric measurements [10][11][12]. Fluorescein stain could stain stroma while leaving the intact epithelium with a specific fluorescein dye, thereby demarcating the location and area of the epithelial loss in ocular surface diseases, on a relative macro scale as well [13].…”
mentioning
confidence: 99%
“…Slit-lamp photography is classically performed by a permanently mounted camera, which often requires a computer system for data storage and network connectivity [ 1 ]. In addition, such mounted slit-lamp cameras require a significant amount of clinic space, are stationery that limits their use to a single examination lane, and require operation by trained technicians or physicians [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The cost is prohibitive, and as a result many ophthalmology departments do not have photography access. Studies have shown that image quality from digital cameras mounted to the slit-lamp eye piece are comparable to formal slit-lamp cameras [ 10 ] and recent developments of slide-on magnification lenses with LED lights, have meant that high-resolution anterior segment photographs can be taken with smartphones without a slit-lamp. With 99% of doctors and 95% of nurses in the UK owning a smartphone [ 11 ], this is technology that can be harnessed over a wide range of clinical scenarios and has the potential to significantly aid ophthalmic care.…”
Section: Introductionmentioning
confidence: 99%